HAFALAN AL-QUR’AN MURID TPA BAITUL MAKMUR DI JORONG JAMBAK KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Kumala Sari Rahmawati; Hayati Hayati; Alimir Alimir; Jasmienti Jasmienti (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this study was to determine the memorization of the Qur'an by the students of Baitul Makmur TPA Jorong Jambak, Luhak Nan Duo District, West Pasaman Regency. Memorizing the Qur'an is one of the subjects at Baitul Makmur TPA. Which at Baitul Makmur TPA has a program before students graduate from Baitul Makmur TPA must memorize juz 'amma first. In this case, of course, it does not always run smoothly, there will be obstacles to be faced. Considering that each student's ability to memorize the Qur'an is different, some are fast, some are slow, some have memorized it but for a few weeks forget to memorize it. The problem in this thesis is: there are students who do not survive their memorization. The purpose of the author's research is to find out what causes the memorization of juz 'amma in TPA Baitul Makmur students does not persist, the supporting and inhibiting factors for memorizing juz 'amma in TPA Baitul Makmur students in Jorong Jambak, Luhak Nan Duo District, West Pasaman Regency. This research is a field research research, with a qualitative descriptive approach, in this study the author describes the problems that exist in the field according to the facts that the authors find in the field while the data collection techniques in this study are interviews and documentation. The author uses key informants and supporters to obtain data. The data analysis used in this research is data reduction, display and verification. Based on the results of this study, it shows that students whose memorization does not last long, this happens because there are students who are less aware of the importance of memorizing, memorizing because it is not often repeated at home, memorizing only at the TPA, playing mobile phones more often, memorizing limited to memorization wants to go home quickly because those who memorize it can go home quickly. And also the conditions and atmosphere of children's learning that affect the memorization of the Baitul Makmur TPA students, namely the atmosphere is not conducive and there are children who do not focus on memorizing because there is noise that interferes with the focus of students in memorizing. Keyword: Memorization, Al-Qur'an